The internal field in a ferromagnetic crystal with chiral molecular packing of achiral organic radicals - Blundell, SJ; Lancaster, T; Baker, PJ; Pratt, FL; Shiomi, D; Sato, K; Takui, T (MDPI, 2021)
The achiral organic radical dinitrophenyl nitronyl nitroxide crystallizes in two enantiomorphs, both being chiral tetragonal space groups that are mirror images of each other. Muon-spin rotation experiments have been performed to study the magnetic properties of these crystals and demonstrate that long-range magnetic order is established below a temperature of 1.10(1) K. Two oscillatory components are detected in the muon data, which show two different temperature dependences.